Revitalisasi Pasar Rakyat Modern dalam Penguataan Ekonomi Umat: (Studi pada Pasar Terpadu Dinoyo Kota Malang) - Mochamad Mukhlis (Program Studi Ekonomi Syariah Institut Agama Islam Sunan Kalijogo Malang, 2019)
The Modern People's Market Revitalization Program today needs to be developed and pursued, given the challenges in the era of 4.0 customers are reluctant to leave the house and are not complicated. Simply open the android application, select the message, pay to the bank, just wait for the ordered item to be able to count the hours the item will arrive at the customer. This study aims to describe the challenges of forming a modern market by the government so that it is right on target. As well as evaluating market managers so that Asar comes alive and develops. In the study, there were three programs needed to revitalize the modern market. The first is the PTD Potential, how potential PTD opportunities can be read by investors to invest in Dinoyo Market. The hope is that the shanty shop is open so that the pace of the economy in PTD goes normally progressing rapidly. The two solutions to the constraints, the traders' aspirations, complaints from visitors must be a large PR (Home Job) manager and government. The third is the touch of spiritual values ​​and the breakthrough of the present, this can be done in collaboration with campuses, UMKM and creative industries. Soft loans for financial institutions can be in the form of KUR, sharia profit sharing systems and capital of traders who are free of usury.